An Innovative Approach to the Synthesis of PMMA/PEG/Nanobifiller Filled Nanocomposites with Enhanced Mechanical and Thermal Properties. Issue 4 (4th March 2019) - Jabeen, Saira; Gul, Sagheer; Kausar, Ayesha; Muhammad, Bakhtiar; Farooq, Muhammad
ABSTRACT: A facile route was adopted to blend the matrix. The PMMA/PEG blend was reinforced with three types of nanofillers, i.e., pristine MWCNT (P-CNT), amine functionalized MWCNT (PDA-EA-CNT) and nanobifiller i.e. nanodiamond functional MWCNT (PDA-EA-CNT-ND) to yield three different types of nanocomposites i.e. PMMA/PEG/P-CNT, PMMA/PEG/PDA-EA-CNT and PMMA/PEG/PDA-EA-CNT-ND. These nanocomposites were reinforced with nanofiller loading (1 wt. %, 3 wt. %, 5 wt. %, 10 wt. %, 30 wt. % and 50 wt. %) by solution casting method. Structure of composite and nanofillers was confirmed by FTIR. FESEM imaging revealed that nanocomposites have micro porous morphology. At high magnification, distribution of functionalized CNT/ND appears to be protruding out of the polymeric matrix. The TGA result suggests that the thermal stability of the nanocomposites was enhanced in comparison to PMMA due to grafting of filler molecules with PMMA/PEG macromolecules. The DTG results showed that the bifiller nanocomposites (PMMA/PEG/PDA-EA-CNT-ND) exhibited improved thermal stability with Tmax (431 ° C) as compared to P-CNT and amine functionalized CNT (PMMA/PEG/PDA-EA-CNT) with Tmax of 395 ° C and 418 ° C respectively. XRD results showed fine interaction between filler and the polymeric matrix. As the filler loading was increased the composites showed pronounced XRD peak at 25.9 °, corresponding to (002) reflection of nanotubes. Significant improvement in the mechanical properties of composites was recorded with the reinforcement of fillers as compared to the neat matrix. The most significant improvement in tensile strength and elastic modulus was observed for the bifiller nanocomposites with 5 wt. % PDA-EA-CNT-ND. They showed a tensile strength and elastic modulus of 29.9 MPa and 1474.31 MPa respectively as compared to amine functionalized CNT with tensile strength (25.7) and elastic modulus (1466.99 MPa)and P-CNT with tensile strength(25 MPa) and elastic modulus (1155.75 MPa). GRAPHICAL ABSTRACT: